Faktor risiko loss to follow up terapi ARV pada pasien HIV - Listy Handayani; Riris Andono Ahmad; Yanri Wijayanti Subronto (Berita Kedokteran Masyarakat (BKM), 2017)
Risk factors for loss to follow up of antiretroviral therapy in HIV patientsPurposeThis study aimed to determine risk factors for loss to follow-up of antiretroviral therapy among HIV-infected patients in Dr. Sardjito Yogyakarta, 2011-2014.MethodsA retrospective cohort study was conducted involving 499 HIV patients. Observations were conducted for four years using medical records. Data analysis was performed using Kaplan-Meier and Cox proportional hazards regression tests.ResultsThere were 190 loss to follow-up patients. Risk factors for loss to follow-up of ARV therapy were: a student (AHR = 2.42; 95% CI = 1.20-4.89), the distance ≥ 10 km (AHR = 1.58; 95% CI = 1:09 to 2:31), using health insurance (AHR = 1.67; 95% CI = 1:11 to 2:51) and homosexual as a protective factor of loss to follow-up of antiretroviral therapy (HR = 0:49; 95% CI = 0.30-0.80).ConclusionBeing a college student, the distance between home and ARV service ≥10 km and using health insurance were the risk factors for loss to follow-up of ARV treatment. Adherence counseling for students, cooperation with the drug taking supervisor and decentralization ARV service, as well as effective and efficient services for patients who use health insurance need to be strengthened.